Low-moisture-absorption nylon composite material and preparation method thereof
By using modified nylon 6 and reinforcing fillers such as halloysite and boron nitride in nylon composite materials, the problems of high water absorption and insufficient flame retardant properties of nylon materials are solved, and the material's low water absorption, high toughness and excellent flame retardancy are achieved. performance.
Patent Information
- Application Number
- CN202411568614.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Nylon materials have problems of degraded mechanical properties and high water absorption under certain conditions, which affect the mechanical properties, processing properties and dielectric properties of the parts.
The preparation method of low -moisture -absorbing nylon composite materials includes the use of nylon 66 and modified nylon 6 as the base material, and add enhanced fillers such as Ellow Stone and boron nitride for synergy to reduce water absorption and improve flame retardant performance.
Significantly improves the toughness and flame retardant properties of nylon composite materials, while reducing water absorption and improving the overall performance of the material.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nylon materials, and in particular to a low moisture absorption nylon composite material and a preparation method thereof. Background Art
[0002] Nylon material has the characteristics of high mechanical strength, better wear resistance, good self-lubricating performance, oil resistance, outstanding anti-vibration and sound absorption, chemical resistance, and easy molding and processing. It is currently the largest polyamide plastic. However, under certain conditions, nylon has disadvantages such as decreased mechanical properties and high water absorption during natural placement, especially high water absorption. When nylon absorbs water, the main effects are: 1) affecting the mechanical properties of the product; 2) affecting the processing performance of the product; 3) affecting the dielectric properties of the product.
[0003] At present, the main ways to reduce the water absorption of nylon materials are blending modification, filling and reinforcement modification, surface treatment, nano-composite modification, etc. Among them, adding inorganic fillers for modification can not only keep the performance of nylon composite materials stable and reduce water absorption, but also improve the comprehensive performance of materials and reduce the cost of nylon materials. In addition, considering the different application requirements, it is also necessary to improve the flame retardant properties and toughness of nylon composite materials. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a low moisture absorption nylon composite material and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A low moisture absorption nylon composite material comprises the following raw materials in parts by weight: 40-50 parts of nylon 66, 55-55 parts of modified nylon 63, 25-35 parts of reinforcing filler, 0.5-2 parts of lubricant, and 0.5-1 parts of antioxidant;
[0007] The modified nylon 6 is prepared by the following steps:
[0008] Step A1, allylamine and sodium hydroxide are dispersed in acetonitrile, recorded as mixed solution 1; 1,3-propylenediamine and sodium hydroxide are dispersed in acetonitrile, recorded as mixed solution 2; cyanuric chloride and acetonitrile are mixed in an ice water bath, mixed solution 1 is slowly added dropwise, and reacted at 0°C for 2-4h, then 1 / 2 volume of mixed solution 2 is slowly added, and reacted at 45-55°C for 3-5h, then heated to 90°C, the remaining mixed solution 2 is slowly added, and the temperature is maintained for reaction for 8-10h, to obtain a functional monomer;
[0009] Step A2, mixing and stirring the Ziegler-Natta catalyst in n-hexane to be uniform, recorded as the catalyst solution; after introducing ethylene into the flask, n-hexane, lauryl acrylate, functional monomer, vinyltrichlorosilane, and triethylaluminum are added in sequence for activation for 5-10 minutes, and then the catalyst solution is added, and the temperature is raised to 45° C., reacted at 0.1 MPa for 25-35 minutes, and then transferred to nitrogen conditions, hydroxy silicone oil and triethylamine are added to react at room temperature for 2.5-3.5 hours, washed, and dried to obtain functionalized polyethylene;
[0010] Step A3, caprolactam, concentrated phosphoric acid and deionized water are mixed evenly, refluxed under nitrogen at 230-260°C for 3-4h, then polycondensed under reduced pressure at 270-280°C for 5-10min, functionalized polyethylene is added to react for 20-30min, and polycondensed under reduced pressure again for 5-10min to obtain modified nylon 6;
[0011] Further, in step A1, the usage ratio of cyanuric chloride, acetonitrile, mixed solution 1 and mixed solution 2 is 0.01-0.03 mol: 100 mL: 50 mL: 100 mL;
[0012] Further, in step A1, the ratio of allylamine, sodium hydroxide and acetonitrile in the mixed solution 1 is 0.01-0.03 mol: 0.05-0.1 g: 50 mL, and the ratio of 1,3-propylenediamine, sodium hydroxide and acetonitrile in the mixed solution 2 is 0.02-0.06 mol: 0.1-0.2 g: 100 mL;
[0013] Further, in step A2, the dosage ratio of n-hexane, lauryl acrylate, functional monomer, vinyl trichlorosilane, triethylaluminum, catalyst solution, hydroxy silicone oil and triethylamine is 20-60mL: 0.01-0.02mol: 0.005-0.015mol: 0.001-0.005mol: 0.05-0.1mL: 20mL: 1-3mL: 5-10g, and the dosage ratio of Ziegler-Natta catalyst and n-hexane in the catalyst solution is 0.001-0.005g: 20mL;
[0014] Furthermore, in step A3, the usage ratio of caprolactam, concentrated phosphoric acid, deionized water and functionalized polyethylene is 100g: 1-3g: 1-2g: 1-3g.
[0015] The reinforcing filler is prepared by the following steps:
[0016] Step B1, dispersing the halloysite nanotubes in 1 mol / L Tris-HCl buffer solution with a pH of 8.5 and deionized water, adding dopamine hydrochloride and stirring to react for 8-12 hours, centrifuging, washing, and drying to obtain PDA@haloysite;
[0017] Step B2, mixing boron nitride powder and 98wt% concentrated sulfuric acid for 5-10h, pouring into deionized water for ultrasonic treatment for 40-60min, filtering and washing until the pH value of the filtrate is 6-8, collecting the filter residue, and redispersing it in deionized water, standing for 12-24h, taking the supernatant, centrifuging again, and collecting boron nitride nanosheets; adding boron nitride nanosheets and PDA@halloysite into deionized water and stirring for 24h to obtain a reinforced filler;
[0018] Further, in step B1, the usage ratio of halloysite nanotubes, Tris-HCl buffer solution, deionized water and dopamine hydrochloride is 0.5-2 g: 2-4 mL: 100 mL: 0.2-0.6 g;
[0019] Further, in step B2, the mass ratio of boron nitride nanosheets, PDA@halloysite and deionized water is 0.5-1:1-3:20;
[0020] Furthermore, in step B2, the dosage ratio of boron nitride powder to concentrated sulfuric acid is 0.1-3 g:10 mL.
[0021] A method for preparing a low moisture absorption nylon composite material comprises the following steps:
[0022] Step S1, weighing raw materials by weight, stirring and mixing reinforcing fillers, lubricants and antioxidants to obtain a premix;
[0023] Step S2, uniformly mixing nylon 66, modified nylon 6 and the premix to obtain a nylon mixture;
[0024] Step S3, putting the nylon mixture into a twin-screw extruder, extruding and granulating at 260-280° C. to obtain a nylon composite material.
[0025] Beneficial effects of the present invention:
[0026] The nylon composite material prepared by the present invention is prepared by using nylon 66 and modified nylon 6 as base materials, adding auxiliary agents such as reinforcing fillers, mixing, and extruding granulation; the introduction of modified nylon 6 improves the toughness of the composite material and reduces the water absorption rate; and the introduction of the reinforcing filler can utilize the synergistic effect of halloysite and boron nitride to improve the flame retardant property of the composite material and further reduce the water absorption rate.
[0027] In the modified nylon 6, cyanuric chloride is first reacted with allylamine and 1,3-propylenediamine to obtain a functional monomer containing terminal amino groups and double bond structures; the double bonds in the functional monomers are then copolymerized with lauryl acrylate, vinyltrichlorosilane and ethylene to obtain functionalized polyethylene; finally, the amino groups on the side chains of the functionalized polyethylene react with the products of caprolactam ring opening and polycondensation to obtain modified nylon 6. The introduction of modified nylon 6 significantly improves the toughness of nylon composite materials and reduces the water absorption of composite materials; the introduction of functionalized polyethylene reduces the water absorption of composite materials, which is because the non-polar polyethylene long chain can effectively hinder the contact between nylon composite materials and water molecules and reduce the water absorption rate. At the same time, the hydrophobic long chain structure and silicon atoms contained in the functionalized polyethylene also improve the hydrophobicity of the composite material, reducing the water absorption of the composite material; in addition, the toughness of the composite material can be improved, which is because the yield strength of polyethylene is lower than that of nylon, which can effectively improve the brittleness of nylon at low temperatures, thereby improving its overall performance. Functionalized polyethylene is introduced into nylon by chemical bonding, which not only improves the toughness of nylon and reduces water absorption, but also improves the stability of nylon composite materials.
[0028] In the reinforcing filler, dopamine hydrochloride is first used as the raw material to coat the surface of halloysite nanotubes with polydopamine to obtain PDA@haloysite; then, the strong adsorption of polydopamine is used to compound halloysite and boron nitride to obtain reinforcing filler. The introduction of reinforcing filler not only reduces the water absorption of nylon composite materials, but also improves the flame retardant properties of composite materials; the reduction in water absorption is due to the synergistic effect of halloysite and boron nitride in the reinforcing filler, which on the one hand limits the vibration space of nylon molecular chains, and on the other hand can use their unique nanotube structure and lamellar structure to increase the diffusion distance of water molecules in the matrix, prevent water molecules in the air from diffusing to the internal amorphous area, thereby reducing the water absorption rate of nylon composite materials; and the synergistic effect of halloysite, boron nitride and modified nylon 6 containing triazine structure can effectively improve the flame retardant properties of composite materials. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] Modified nylon 6 is prepared by the following steps:
[0032] Step A1, 0.01 mol of allylamine and 0.05 g of sodium hydroxide are dispersed in 50 mL of acetonitrile, recorded as mixed solution 1; 0.02 mol of 1,3-propylenediamine and 0.1 g of sodium hydroxide are dispersed in 100 mL of acetonitrile, recorded as mixed solution 2; 0.01 mol of cyanuric chloride and 100 mL of acetonitrile are mixed in an ice-water bath, 50 mL of mixed solution 1 is slowly added dropwise, and reacted at 0° C. for 2 h, then 50 mL of mixed solution 2 is slowly added, and reacted at 45° C. for 3 h, then the temperature is raised to 90° C., 50 mL of mixed solution 2 is slowly added, and the temperature is maintained for reaction for 8 h, to obtain a functional monomer;
[0033] Step A2, 0.001g Ziegler-Natta catalyst was mixed and stirred in 20mL n-hexane, which was recorded as catalyst solution; after ethylene was introduced into the flask, 20mL n-hexane, 0.01mol lauryl acrylate, 0.005mol functional monomer, 0.001mol vinyltrichlorosilane, and 0.05mL triethylaluminum were added in sequence for activation for 5min, and then 20mL catalyst solution was added, and the temperature was raised to 45°C, and the reaction was carried out at 0.1MPa for 25min, and then transferred to nitrogen conditions, 1mL hydroxy silicone oil and 5g triethylamine were added, and the reaction was carried out at room temperature for 2.5h, and then washed and dried to obtain functionalized polyethylene;
[0034] Step A3, mix 100g of caprolactam, 1g of concentrated phosphoric acid and 1g of deionized water evenly, reflux under nitrogen at 230°C for 3h, then polymerize under reduced pressure at 270°C for 5min, add 1g of functionalized polyethylene to react for 20min, and polymerize under reduced pressure again for 5min to obtain modified nylon 6.
[0035] The reinforced filler is prepared by the following steps:
[0036] Step B1, dispersing 0.5 g of halloysite nanotubes in 2 mL of 1 mol / L Tris-HCl buffer solution with a pH of 8.5 and 100 mL of deionized water, adding 0.2 g of dopamine hydrochloride and stirring for 8 h, centrifuging, washing, and drying to obtain PDA@haloysite;
[0037] Step B2, 0.1g of boron nitride powder and 10mL of 98wt% concentrated sulfuric acid were mixed and stirred for 5h, poured into deionized water for ultrasonic treatment for 40min, filtered and washed until the pH of the filtrate was 6, then the filter residue was collected and redispersed in deionized water, allowed to stand for 12h, the supernatant was taken, and centrifuged again to collect boron nitride nanosheets; 0.5g of boron nitride nanosheets and 1g of PDA@halloysite were added to 20g of deionized water and stirred for 24h to obtain a reinforced filler.
[0038] Example 2
[0039] Modified nylon 6 is prepared by the following steps:
[0040] Step A1, 0.02 mol of allylamine and 0.07 g of sodium hydroxide were dispersed in 50 mL of acetonitrile, recorded as mixed solution 1; 0.04 mol of 1,3-propylenediamine and 0.15 g of sodium hydroxide were dispersed in 100 mL of acetonitrile, recorded as mixed solution 2; 0.02 mol of cyanuric chloride and 100 mL of acetonitrile were mixed in an ice-water bath, 50 mL of mixed solution 1 was slowly added dropwise, and reacted at 0°C for 3 h, and then 50 mL of mixed solution 2 was slowly added, and reacted at 50°C for 4 h, and then the temperature was raised to 90°C, 50 mL of mixed solution 2 was slowly added, and the temperature was maintained for 9 h to obtain a functional monomer;
[0041] Step A2, 0.003 g of Ziegler-Natta catalyst was mixed and stirred in 20 mL of n-hexane, which was recorded as a catalyst solution; after ethylene was introduced into the flask, 40 mL of n-hexane, 0.015 mol of lauryl acrylate, 0.01 mol of functional monomer, 0.003 mol of vinyltrichlorosilane, and 0.07 mL of triethylaluminum were added in sequence for activation for 7 min, and then 20 mL of the catalyst solution was added, and the temperature was raised to 45° C., and the reaction was carried out at 0.1 MPa for 30 min, and then transferred to nitrogen conditions, 2 mL of hydroxy silicone oil and 7 g of triethylamine were added for reaction at room temperature for 3 h, and then washed and dried to obtain functionalized polyethylene;
[0042] Step A3, mix 100g of caprolactam, 2g of concentrated phosphoric acid and 1.5g of deionized water evenly, reflux under nitrogen at 250°C for 3.5h, then polymerize under reduced pressure at 275°C for 7min, add 2g of functionalized polyethylene to react for 25min, and polymerize under reduced pressure again for 7min to obtain modified nylon 6.
[0043] The reinforced filler is prepared by the following steps:
[0044] Step B1, dispersing 1 g of halloysite nanotubes in 3 mL of 1 mol / L Tris-HCl buffer solution with a pH of 8.5 and 100 mL of deionized water, adding 0.4 g of dopamine hydrochloride and stirring for 10 h, centrifuging, washing, and drying to obtain PDA@haloysite;
[0045] Step B2, 1g of boron nitride powder and 10mL of 98wt% concentrated sulfuric acid were mixed and stirred for 7h, poured into deionized water for ultrasonic treatment for 50min, filtered and washed until the pH of the filtrate was 7, then the filter residue was collected and redispersed in deionized water, allowed to stand for 18h, the supernatant was taken, and centrifuged again to collect boron nitride nanosheets; 0.7g of boron nitride nanosheets and 2g of PDA@halloysite were added to 20g of deionized water and stirred for 24h to obtain a reinforced filler.
[0046] Example 3
[0047] Modified nylon 6 is prepared by the following steps:
[0048] Step A1, 0.03 mol of allylamine and 0.1 g of sodium hydroxide are dispersed in 50 mL of acetonitrile, recorded as mixed solution 1; 0.06 mol of 1,3-propylenediamine and 0.2 g of sodium hydroxide are dispersed in 100 mL of acetonitrile, recorded as mixed solution 2; 0.03 mol of cyanuric chloride and 100 mL of acetonitrile are mixed in an ice-water bath, 50 mL of mixed solution 1 is slowly added dropwise, and reacted at 0° C. for 4 h, then 50 mL of mixed solution 2 is slowly added, and reacted at 55° C. for 3-5 h, then the temperature is raised to 90° C., 50 mL of mixed solution 2 is slowly added, and the temperature is maintained for reaction for 10 h, to obtain a functional monomer;
[0049] Step A2, 0.005 g of Ziegler-Natta catalyst was mixed and stirred in 20 mL of n-hexane, which was recorded as a catalyst solution; after ethylene was introduced into the flask, 60 mL of n-hexane, 0.02 mol of lauryl acrylate, 0.015 mol of functional monomer, 0.005 mol of vinyltrichlorosilane, and 0.1 mL of triethylaluminum were added in sequence for activation for 10 min, and then 20 mL of the catalyst solution was added, and the temperature was raised to 45° C., and the reaction was carried out at 0.1 MPa for 35 min, and then transferred to nitrogen conditions, 3 mL of hydroxy silicone oil and 10 g of triethylamine were added, and the reaction was carried out at room temperature for 3.5 h, and then washed and dried to obtain functionalized polyethylene;
[0050] Step A3, mix 100g of caprolactam, 3g of concentrated phosphoric acid and 2g of deionized water, reflux under nitrogen at 260°C for 4h, then polycondense under reduced pressure at 280°C for 10min, add 3g of functionalized polyethylene to react for 30min, and polycondense under reduced pressure again for 10min to obtain modified nylon 6.
[0051] The reinforced filler is prepared by the following steps:
[0052] Step B1, dispersing 2 g of halloysite nanotubes in 4 mL of 1 mol / L Tris-HCl buffer solution with a pH of 8.5 and 100 mL of deionized water, adding 0.6 g of dopamine hydrochloride and stirring for 12 h, centrifuging, washing, and drying to obtain PDA@haloysite;
[0053] Step B2, 3g of boron nitride powder and 10mL of 98wt% concentrated sulfuric acid were mixed and stirred for 10h, poured into deionized water for ultrasonic treatment for 60min, filtered and washed until the pH of the filtrate was 8, then the filter residue was collected and redispersed in deionized water, allowed to stand for 24h, the supernatant was taken, and centrifuged again to collect boron nitride nanosheets; 1g of boron nitride nanosheets and 3g of PDA@halloysite were added to 20g of deionized water and stirred for 24h to obtain a reinforced filler.
[0054] Example 4
[0055] A method for preparing a low moisture absorption nylon composite material comprises the following steps:
[0056] 6640 parts of nylon, 635 parts of modified nylon prepared in Example 1, 25 parts of reinforcing filler prepared in Example 1, 0.5 parts of lubricant (calcium stearate), and 10980.5 parts of antioxidant;
[0057] Step S1, weighing raw materials by weight, stirring and mixing the reinforcing filler, lubricant (calcium stearate) and antioxidant 1098 prepared in Example 1 to obtain a premix;
[0058] Step S2, uniformly mixing nylon 66, modified nylon 6 prepared in Example 1 and the premix to obtain a nylon mixture;
[0059] Step S3, putting the nylon mixture into a twin-screw extruder, and extruding and granulating at 260° C. to obtain a nylon composite material.
[0060] Example 5
[0061] A method for preparing a low moisture absorption nylon composite material comprises the following steps:
[0062] 6645 parts of nylon, 645 parts of modified nylon prepared in Example 2, 30 parts of reinforcing filler prepared in Example 2, 1 part of lubricant (calcium stearate), and 10980.8 parts of antioxidant;
[0063] Step S1, weighing raw materials by weight, stirring and mixing the reinforcing filler, lubricant (calcium stearate) and antioxidant 1098 prepared in Example 2 to obtain a premix;
[0064] Step S2, uniformly mixing nylon 66, modified nylon 6 prepared in Example 2 and the premix to obtain a nylon mixture;
[0065] Step S3, putting the nylon mixture into a twin-screw extruder, and extruding and granulating at 270° C. to obtain a nylon composite material.
[0066] Example 6
[0067] A method for preparing a low moisture absorption nylon composite material comprises the following steps:
[0068] 6650 parts of nylon, 655 parts of modified nylon prepared in Example 3, 35 parts of reinforcing filler prepared in Example 3, 2 parts of lubricant (calcium stearate), and 10981 parts of antioxidant;
[0069] Step S1, weighing raw materials by weight, stirring and mixing the reinforcing filler, lubricant (calcium stearate) and antioxidant 1098 prepared in Example 3 to obtain a premix;
[0070] Step S2, uniformly mixing nylon 66, modified nylon 6 prepared in Example 3 and the premix to obtain a nylon mixture;
[0071] Step S3, putting the nylon mixture into a twin-screw extruder, and extruding and granulating at 280° C. to obtain a nylon composite material.
[0072] Comparative Example 1
[0073] This comparative example is a nylon composite material, which differs from Example 6 in that nylon 6 is used instead of the modified nylon 6 prepared in Example 3, and the rest are the same.
[0074] Comparative Example 2
[0075] This comparative example is a nylon composite material, which is different from Example 6 in that halloysite is used instead of the reinforcing filler prepared in Example 3, and the rest is the same.
[0076] The performance tests were performed on the samples prepared in Examples 4-6 and Comparative Examples 1-2:
[0077] Flame retardancy test: tested in accordance with UL-94 standard;
[0078] Water absorption performance test: Use ASTMD570-2005 "Test method for water absorption of plastics", soak for 24 hours at 23℃, and test the water absorption rate;
[0079] Tensile strength test: tensile strength test is carried out according to ASTM-D638 "Standard Test Method for Tensile Properties of Plastics";
[0080] Contact angle test: Use a contact angle meter to measure the static contact angle of a water drop on the surface of a nylon material;
[0081] The test results are shown in the following table:
[0082] Flame retardant Water absorption (%) Tensile strength(MPa) Contact angle (°) Example 4 V0 0.57 58.6 106 Example 5 V0 0.55 59.4 108 Example 6 V0 0.54 61.3 111 Comparative Example 1 V0 1.31 45.1 86 Comparative Example 2 V1 1.27 52.6 95
[0083] As can be seen from the above table, the nylon composite material prepared by the present invention has a flame retardant grade of V0 after flame retardancy, water absorption, tensile strength and contact angle tests, a water absorption in the range of 0.54%-0.57%, a tensile strength in the range of 58.6MPa-61.3MPa, and a contact angle in the range of 106°-111°, indicating that the nylon composite material has excellent flame retardancy, toughness and low water absorption.
[0084] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A low moisture absorption nylon composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 40-50 parts of nylon 66, 35-55 parts of modified nylon 6, 25-35 parts of reinforcing filler, 0.5-2 parts of lubricant, and 0.5-1 parts of antioxidant; The modified nylon 6 is prepared by the following steps: Step A1, allylamine and sodium hydroxide are dispersed in acetonitrile, recorded as mixed solution 1; 1,3-propylenediamine and sodium hydroxide are dispersed in acetonitrile, recorded as mixed solution 2; cyanuric chloride and acetonitrile are mixed in an ice water bath, mixed solution 1 is slowly added dropwise, and reacted at 0°C for 2-4h, then 1 / 2 volume of mixed solution 2 is slowly added, and reacted at 45-55°C for 3-5h, then heated to 90°C, the remaining mixed solution 2 is slowly added, and the temperature is maintained for reaction for 8-10h, to obtain a functional monomer; Step A2, mixing and stirring the Ziegler-Natta catalyst in n-hexane to be uniform, recorded as the catalyst solution; after introducing ethylene into the flask, n-hexane, lauryl acrylate, functional monomer, vinyltrichlorosilane, and triethylaluminum are added in sequence for activation for 5-10 minutes, and then the catalyst solution is added, and the temperature is raised to 45° C., reacted at 0.1 MPa for 25-35 minutes, and then transferred to nitrogen conditions, hydroxy silicone oil and triethylamine are added to react at room temperature for 2.5-3.5 hours, washed, and dried to obtain functionalized polyethylene; Step A3, mix caprolactam, concentrated phosphoric acid and deionized water evenly, reflux under nitrogen at 230-260°C for 3-4h, then polymerize under reduced pressure at 270-280°C for 5-10min, add functionalized polyethylene to react for 20-30min, and polymerize under reduced pressure again for 5-10min to obtain modified nylon 6.
2. The low moisture absorption nylon composite material according to claim 1, characterized in that: In step A1, the usage ratio of cyanuric chloride, acetonitrile, mixed solution 1 and mixed solution 2 is 0.01-0.03 mol:100 mL:50 mL:100 mL.
3. The low moisture absorption nylon composite material according to claim 1, characterized in that: In step A1, the usage ratio of allylamine, sodium hydroxide and acetonitrile in mixed solution 1 is 0.01-0.03 mol: 0.05-0.1 g: 50 mL, and the usage ratio of 1,3-propylenediamine, sodium hydroxide and acetonitrile in mixed solution 2 is 0.02-0.06 mol: 0.1-0.2 g: 100 mL.
4. The low moisture absorption nylon composite material according to claim 1, characterized in that: In step A2, the dosage ratio of n-hexane, lauryl acrylate, functional monomer, vinyl trichlorosilane, triethylaluminum, catalyst solution, hydroxy silicone oil and triethylamine is 20-60 mL: 0.01-0.02mol:0.005-0.015mol:0.001-0.005mol:0.05-0.1mL:20mL:1-3mL:5-10g, the dosage ratio of Ziegler-Natta catalyst and n-hexane in the catalyst solution is 0.001-0.005g:20mL.
5. The low moisture absorption nylon composite material according to claim 1, characterized in that: In step A3, the usage ratio of caprolactam, concentrated phosphoric acid, deionized water and functionalized polyethylene is 100 g: 1-3 g: 1-2 g: 1-3 g.
6. The low moisture absorption nylon composite material according to claim 1, characterized in that: The reinforcing filler is prepared by the following steps: Step B1, dispersing the halloysite nanotubes in 1 mol / L Tris-HCl buffer solution with a pH of 8.5 and deionized water, adding dopamine hydrochloride and stirring to react for 8-12 hours, centrifuging, washing, and drying to obtain PDA@haloysite; Step B2, mixing boron nitride powder and 98wt% concentrated sulfuric acid for 5-10h, pouring into deionized water for ultrasonic treatment for 40-60min, filtering and washing until the pH value of the filtrate is 6-8, collecting the filter residue, and redispersing it in deionized water, standing for 12-24h, taking the supernatant, centrifuging again, and collecting boron nitride nanosheets; adding boron nitride nanosheets and PDA@halloysite into deionized water and stirring for 24h to obtain a reinforced filler.
7. The low moisture absorption nylon composite material according to claim 6, characterized in that: In step B1, the usage ratio of halloysite nanotubes, Tris-HCl buffer solution, deionized water and dopamine hydrochloride is 0.5-2 g: 2-4 mL: 100 mL: 0.2-0.6 g.
8. The low moisture absorption nylon composite material according to claim 6, characterized in that: In step B2, the mass ratio of boron nitride nanosheets, PDA@halloysite and deionized water is 0.5-1:1-3:
20.
9. The low moisture absorption nylon composite material according to claim 6, characterized in that: In step B2, the dosage ratio of boron nitride powder to concentrated sulfuric acid is 0.1-3 g:10 mL.
10. A method for preparing the low moisture absorption nylon composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step S1, weighing raw materials by weight, stirring and mixing reinforcing fillers, lubricants and antioxidants to obtain a premix; Step S2, uniformly mixing nylon 66, modified nylon 6 and the premix to obtain a nylon mixture; Step S3, putting the nylon mixture into a twin-screw extruder, extruding and granulating at 260-280° C. to obtain a nylon composite material.
Citation Information
Patent Citations
Precipitation-free, low-water-absorption, halogen-free and flame-retardant reinforced nylon 66 as well as preparation method and application thereof
CN112920598A
Cited By
Corrosion-resistant composite material, preparation method and application of corrosion-resistant composite material in gear
CN120966238A
Corrosion-resistant composite material, method of manufacture and use thereof in gears
CN120966238B